Nanowire Field-Effect Transistor (FET) - García-Loureiro, Antonio; Kalna, Karol; Seoane, Natalia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In the last few years, the leading semiconductor industries have introduced multi-gate non-planar transistors into their core business. These are being applied in memories and in logical integrated circuits to achieve better integration on the chip, increased performance, and reduced energy consumption. Intense research is underway to develop these devices further and to address their limitations, in order to continue transistor scaling while further improving performance. This Special Issue looks at recent developments in the field of nanowire field-effect transistors (NW-FETs), covering different aspects of the technology, physics, and modelling of these nanoscale devices.